Peningkatan kesadaran akan skrining non-invasif risiko prediabetes pada komunitas usia produktif - Iche Liberty; Pariyana Pariyana; Eddy Roflin; Muhammad Aziz; Mira Maulani Fatima (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Raising awareness of non-invasive screening of risk of prediabetes in productive age communities. Productive age groups of people are vulnerable to prediabetes. One solution to increase awareness of these risk communities is to provide comprehensive knowledge enhancement that screening with the measurement of the TyG Index and several body anthropometries is non-invasive, easy, and inexpensive to prevent the risk of prediabetes and its progression. The method of implementing this community service activity is providing motivation in the form of health promotion or counseling. Based on the data obtained from the activities that have been carried out, it can be concluded that there is a tendency that those who have a high BMI tend to have a high TyG Index as well. Therefore, it is recommended that patients always maintain and maintain their weight and abdominal circumference at normal limits according to age. As well as checking blood glucose levels, lipid profiles, and blood pressure regularly at the nearest health service, such as Posbindu or Puskesmas. Increasing comprehensive knowledge that screening with the measurement of the TyG Index and several body anthropometrics such as weight, height, and abdominal circumference is non-invasive and has become one of the solutions to increase awareness of the productive age community in preventing the risk of prediabetes and diabetes mellitus.